La Banca Electrónica: Satisfacción, Confianza y Requerimientos de los clientes y socios residentes de la ciudad de Loja. - Castro Torres, Leidy Victoria (2025)
Currently, technological advances have evolved favorably, managing to establish mechanisms that contribute to competitiveness within the financial system. Technology has made it possible to adopt efficient banking products and services that adjust to the different needs of users. Given this, this research was carried out with the purpose of determining an electronic banking model that generates trust, security or satisfaction among clients and partners. The study has a mixed approach of a transactional, exploratory - descriptive nature since the data are collected within the same period, for this purpose surveys were applied that were directed to 384 banked users. The results obtained show a level of confidence of 68% on the part of users when using the services offered by electronic banking to satisfy their needs. On the other hand, the level of acceptance fluctuates at 72% with room for improvement, considering the implementation or design of new services depending on the institution, which determines an important technological advance in the economic growth of organizations, positioning them within the financial market. Electronic banking has proven to be a powerful tool, allowing customers to carry out their most frequently used operations such as: balance consultation, direct and interbank transfers, payment of services, cell phone recharges, pay TV, credit card payments, bank references, electronic documents among other services that provide daily tasks and enable the bank's global task.